Kinematics of outer halo globular clusters: M 75 and NGC 6426 - Koch-Hansen, Andreas; Hanke, Michael; Kacharov, Nikolay (Astronomy and astrophysics, 2018)
Globular clusters (GCs) and their dynamic interactions with the Galactic components provide an important insight into the structure and formation of the early Milky Way. We present a kinematic study of two outer halo GCs based on a combination of VLT/FORS2, VLT/FLAMES, and Magellan/MIKE low- and high-resolution spectroscopy of 32 and 27 member stars, respectively. Although both clusters are located at Galactocentric distances of 15 kpc, they have otherwise very different properties. M 75 is a luminous and metal-rich system at [Fe/H] = 1.2 dex, which is a value that we confirm from the calcium triplet region. This GC shows mild evidence for rotation with an amplitude of 5 km s . One of the most metal-poor GCs in the Milky Way (at [Fe II/H] = dex), NGC 6426 exhibits marginal evidence of internal rotation at the 2 km s level. Both objects have velocity dispersions that are consistent with their luminosity. Although limited by small-number statistics, the resulting limits on their ratios suggest that M 75 is a slow rotator driven by internal dynamics rather than being affected by the weak Galactic tides at its large distances. In this work, M 75 ( ) is fully consistent with the properties of other, younger halo clusters. At , NGC 6426 appears to have a remarkably ordered internal motion for its low metallicity, but the large uncertainty does not allow for an unambiguous categorization as a fast rotator. An accretion origin of M 75 cannot be excluded, based on the eccentric orbit, which we derived from the recent data release 2 of Gaia, and considering its younger age.